Pembentukan dan Pendampingan Digital English Club di Sekolah Dasar - Gusdian, Rosalin Ismayoeng; Abidasari, Erlyna (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
This community service program aimed at solving the problems of the lack of English skills for Elementary School students. Based on interviews and initial observations, students tend to be shy and reluctant to participate actively during the English learning process. Another problem found is the lack of interactive learning materials and media used by teachers during teaching and learning activities. Therefore, the 'Digital English Club' service program focused on improving students' English skills and teachers' abilities to manage a digital-based English Club. Methods for implementing community service include: 1) Preparing Digital-Based English Learning Media and Resources, 2) Teacher Training Workshops, 3) Establishing Digital English Clubs and 4) Digital English Club Assistance. The results included the creation of digital-based media and learning resources that are used by teachers to create active and interactive English classes and the formation of Digital English Clubs in service partner elementary schools as one of the extracurricular options that can increase students' interest and English skills.